Clival Chondrosarcoma Associated With an Intra-Axial Cystic Medullary Lesion Responsive to Steroids - Walter, Johannes; Kapitza, Sandra; Krayenbühl, Niklaus; Tarnutzer, Alexander A. (Frontiers in Neurology, 2018)
Introduction: Here we present a 75-year-old patient who was admitted with acute-onset right-sided hemiparesis, dysphagia, dysarthria and nystagmus. Repeated MRI scans showed two lesions with contact to one another: one solid stationary extra-axial lesion at the caudal part of the clivus and a rapidly growing intra-axial cystic lesion at the level of the medulla oblongata. Biopsy of the solid lesion demonstrated a low-grade chondrosarcoma, while no tissue sample of the cystic lesion could be retrieved. After initiation of dexamethasone therapy the cystic lesion markedly regressed. Background: A literature search on published cases with the same combination of a stationary solid extra-axial mass at the caudal part of the clivus and a growing intra-axial cystic mass in the medulla oblongata was negative, indicating that the case described here is both unique and novel. Discussion: Considering the rapid progression of symptoms and growth on MR-imaging in combination with the marked response to steroids, an inflammatory response linked to the chondrosarcoma is most likely. At the same time other possible explanations as a second neoplasm, an abscess or an ischemic lesion seem unlikely. Concluding remarks: This case underlines an unusual complication of a rare brainstem tumor and outlines both the differential diagnosis and potential treatment options. For such cystic lesions in combination with chondrosarcoma, a treatment course with steroids should be considered along with surgical exploration necessary to obtain the diagnosis and for potential reduction of mass-effect on the medulla oblongata.